Multi-omics in colorectal cancer liver metastasis: applications and research advances - Kexue Zhou; Chengxiang Yang; Yan Li (Cancer Biology & Medicine)
Colorectal cancer (CRC) is a common malignant tumor with a high mortality rate worldwide. Advanced CRC often leads to liver metastasis, which has a poor prognosis, highlighting the need to investigate the underlying mechanisms. Omics, encompassing genomics, epigenomics, transcriptomics, proteomics, metabolomics, and microbiomics, enables comprehensive molecular analysis of cells and tissues. Tumor-omics research has advanced rapidly, with growing attention on CRC-related omics. However, systematic reviews on omics research specific to colorectal cancer liver metastasis (CRLM) are limited. This review summarizes the current status and progress of multi-omics research on CRLM and discusses the application of multi-omics technologies in basic research and the significant clinical implications.